KAJIAN KEPEMIMPINAN PEREMPUAN DALAM KELUARGA PERSPEKTIF TAFSIR - Hudaya, Hairul (Sunan Kalijaga State Islamic University & The Asia Foundation, 2011)
This article discusses the debates regarding the interpretation of al-Nisa (4) 34 [Holy Quran] that was advocated by many ulama. There exists a significant difference that indicate a greater role for women. Based on the assumption that the leadership of men over women can be absolute, given (wahby)or by effort (kasby), the final views of leadership entails the consequence that not all men can become leaders for women, even in domestic matters. Nevertheless, these two views are still strongly indicative that men are equals to women in all forms of leadership and does no differentiate between domestic or public matters of leadership.